2014
DOI: 10.5343/bms.2012.1097
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of commercial tuna and mackerel in the Indonesian Archipelago

Abstract: While numerous population genetics studies have investigated phylogeographic patterns of coral reef organisms in the coral triangle, few have addressed whether fishes in the pelagic environment exhibit concordant patterns of genetic subdivision. We analyzed approximately 400 base pairs of the mitochondrial control region to compare population structure and phylogeography of five pelagic tuna and mackerel within a subset of their geographic ranges (i.e., the Indonesian Archipelago). Focal species include frigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 52 publications
3
44
0
5
Order By: Relevance
“…The degree to which genetic properties of a single species are representative of other species in the same community is unclear (Kelly and Palumbi 2010, Carpenter et al 2011, Bailey et al 2012. For example, rocky shore fishes and limpets each displayed highly different evolutionary patterns despite being closely related (Bird et al 2007, von der Heyden et al 2013); in contrast, broad geographic scale delineations between evolutionarily distinct populations frequently co-occur (Fortuna et al 2009, Carpenter et al 2011, Jackson et al 2014. Regardless of whether a single species can represent a community, establishing methodologies based on the simple case of a single species is an obvious precursor to more complex scenarios where genetic information from multiple species could be combined.…”
Section: Which Molecular Techniques Measure Which System Attributes?mentioning
confidence: 99%
“…The degree to which genetic properties of a single species are representative of other species in the same community is unclear (Kelly and Palumbi 2010, Carpenter et al 2011, Bailey et al 2012. For example, rocky shore fishes and limpets each displayed highly different evolutionary patterns despite being closely related (Bird et al 2007, von der Heyden et al 2013); in contrast, broad geographic scale delineations between evolutionarily distinct populations frequently co-occur (Fortuna et al 2009, Carpenter et al 2011, Jackson et al 2014. Regardless of whether a single species can represent a community, establishing methodologies based on the simple case of a single species is an obvious precursor to more complex scenarios where genetic information from multiple species could be combined.…”
Section: Which Molecular Techniques Measure Which System Attributes?mentioning
confidence: 99%
“…Tagging experiments (Hurst et al, 1999;Hay and McKinnell, 2002;Block et al, 2005) were also useful in tracking movements of fishes, but were found to be difficult in the case of small pelagic fishes due to their size . Henceforth, genetic data is widely utilized in conservation biology (Schwartz et al, 2007), systematics (Ward et al, 2005;Dasmahapatra and Mallet, 2006;Pedrosa-Gerasmio et al, 2012), and population genetic studies (Pearse and Crandall, 2004;Lemer et al, 2007;Crandall et al, 2000;Allendorf et al, 2012;Palumbi, 2003;Reiss et al, 2009;Santos et al, 2010;Jackson et al, 2014) as it could provide direct measurement and examination of genetic diversity, migration, effective population size and population demographic history (Emerson et al, 2001;Hare et al, 2011;Pearse and Crandall, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…two studies are notable for finding surprisingly high levels of genetic structure in putatively high dispersal taxa: a coral with long-lived larvae (concepcion et al 2014) and five species of pelagic fishes (Jackson et al 2014). together, these studies represent a substantive contribution to our understanding of ecology and evolution in the Indo-Pacific region.…”
Section: Introduction To the Special Issuementioning
confidence: 96%
“…These include corals (concepcion et al 2014, Marti-Puig et al 2014), giant clams (Deboer et al 2014a, lobsters (Iacchei et al 2014), and a number of echinoderms (crandall et al , Liggins et al 2014(crandall et al , skillings et al 2014. Vertebrates are represented by sharks (Giles et al 2014), and a wide spectrum of bony fishes including sardinella (Willette et al 2014b), tuna and mackerel (Jackson et al 2014), and a veritable school of reef fishes (bernardi et al 2014, raynal et al 2014, szabo et. al 2014).…”
Section: Introduction To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation